Association between having a hot spring water supply in the home and prevention of long-term care. - Hayasaka, Shinya; Uchida, Minoru; Hattori, Manori; Watanabe, Hideaki; Ojima, Toshiyuki (Complementary Therapies in Clinical Practice, 2018)
Abstract Background and objective According to basic studies, hot spring use has positive effects on the mind and body. However, the association between habitual hot spring use and prevention of long-term care is unknown. Using long-term care insurance data for the residents of Atami City, Japan, who can choose to install hot spring water supply in their homes, this study aimed to determine the association between the installation of a hot spring water supply in the home and prevention of long-term care. Methods 1. Study design: case-control study 2. Subjects: 2719 residents (754 men, 1965 women) of Atami City, Shizuoka Prefecture, Japan, who received long-term care insurance and were certified as "Needing Support" or "Needing Long-Term Care" as of March 2017. 3. Survey methods: Information on long-term care insurance certification was linked to subjects' care level dating back to their initial certification. Also, the installation (or lack thereof) of hot spring water supply in each subject's home was linked to information on Atami household water use as of March 2017. 4. Analysis methods: The age distribution of the subjects was determined. Initial care status and care status as of March 2017 were then compared for the 2194 subjects who received long-term care certification at least twice. These subjects were classified into two groups: those whose care level had not changed or had improved (no change/improvement group) and those whose care level had worsened (worsening group). Subjects were then compared by sex and initial care level in terms of hot spring installation and percentages of no change/improvement or worsening of care level; odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using the chi-square test. Lastly, the same analysis was performed for all subjects grouped together, and ORs and 95% CIs were calculated using the Mantel-Haenszel test. Results Hot springs were installed in the homes of 2359 subjects overall (86.8%). The no change/improvement group and the worsening group comprised 1192 and 1002 subjects, respectively. Overall, improvement or no change in care level was observed in 1050 subjects (55.2%) in the hot spring group and 142 subjects in the no hot spring group (48.5%). Sex-adjusted OR (95% CI) was 1.311 (1.025–1.677, p = 0.036), which represented a significant association. Having a hot spring water supply in the home may be associated with preventing worsening of care level. Conclusion Having a hot spring water supply in the home may be associated with preventing worsening of care level.